Chryseobacterium lecithinasegens sp. nov., a siderophore-producing bacterium isolated from soil at the bottom of a pond. Issue 12 (8th December 2021) - Kutsuna, Ryo; Mashima, Izumi; Miyoshi-Akiyama, Tohru; Muramatsu, Yuki; Tomida, Junko; Kawamura, Yoshiaki
Abstract : Bacterial strain PAGU 2197 T, which was isolated from soil collected from the bottom of a pond in Japan, is characterized in this study. Cells of strain PAGU 2197 T were aerobic, Gram-negative, short rod-shaped, non-motile, flexirubin-producing, oxidase-positive, catalase-positive and lecithinase-negative. A phylogenetic study based on 16S rRNA gene sequences and multilocus sequence analysis ( gyrB, rpoB and rpoD ) indicated that strain PAGU 2197 T belongs to the genus Chryseobacterium and is a member of an independent lineage including Chryseobacterium tructae CCUG 60111 T (sequence similarity, 95.9 %), Chryseobacterium lactis CCUG 60566 T (93.4 %) and Chryseobacterium viscerum CCUG 60103 T (91.6 %). The average nucleotide identity values were 80.83–85.04 %. Because average nucleotide identity values of 95–96 % exceed the 70 % DNA–DNA hybridization cutoff value for species discrimination, strain PAGU 2197 T represents a novel species in the genus Chryseobacterium . The genome of strain PAGU 2197 T was 4 967 738 bp with a G+C content of 35.5 mol%. The sole respiratory quinone of strain PAGU 2197 T was MK-6; the major cellular fatty acids were iso-C15 : 0, iso-C17 : 0 3OH, summed feature 3 (C16 : 1  ω 7 c and/or C16 : 1  ω 6 c ) and summed feature 9 (iso-C17 : 1  ω 9 c and/or C16 : 0 10-methyl); and the major polar lipids were phosphoglycolipids and phosphatidylethanolamine. These results indicate that strain PAGU 2197 T should be classified as representing a novel species in the genus Chryseobacterium, for which the name Chryseobacterium lecithinasegens sp. nov. is proposed, with strain PAGU 2197 T (=NBRC 114264 T =CCUG 75150 T ) as the type strain.